PENGARUH KEUNGGULAN PRODUK DAN PERSAINGAN TERHADAP KEPUTUSAN PEMBELIAN - Thomas Stanislaus Bondan Kusasmaraningtyas, 07.05.51.0151; Kasmari, Kasmari (Students Journal of Economic and Management, 2012)
The purpose of this research is to test the influences of advantage of product, competitive of price and competitive of not price about buying decision Honda motorcycle in Stikubank Semarang University student. SPSS software for data analysis. The result of the analysis showed that advantage of product significant influences about buying decision. While competitive of price and competitive of not price not significant influences about buying decision. This empirical result indicated that in order to increase buying decision should focus on factors such as:advantage of product, competitive of price, and competitive of not price, because its factors proven has influence toward degree of buying decision. Theoritical implications and suggestions for future research have been elaborated at the end of this study.Key words: advantage of product, competitive of price, competitive of not price, buying decision